2010
DOI: 10.1007/s11557-010-0670-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora chrysanthemi sp. nov., a new species causing root rot of chrysanthemum in Japan

Abstract: A new species of Phytophthora was isolated from stem and root rot of chrysanthemum in the Gifu and Toyama prefectures of Japan. The species differs from other Phytophthora species morphologically, and is characterized by nonpapillate, noncaducous sporangia with internal proliferation, formation of both hyphal swellings and chlamydospores, homothallic nature, distinctive intercalary antheridia, and funnel-shaped oogonia. The new species can grow even at 35°C, with an optimum growth temperature of 30°C in V8 jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…3). Cardinal temperatures for vegetative growth on CPA and size and shape of oogonia (mean 35.4 μm; n=50) and oospores (mean 28.4 μm; n=50) grown on CA were similar to those described for Phytophthora chrysanthemi (Naher et al , 2011). Chlamydospores produced on CPA were slightly larger (mean 44.0 μm; n=50) than reported.…”
Section: Figuresupporting
confidence: 73%
See 1 more Smart Citation
“…3). Cardinal temperatures for vegetative growth on CPA and size and shape of oogonia (mean 35.4 μm; n=50) and oospores (mean 28.4 μm; n=50) grown on CA were similar to those described for Phytophthora chrysanthemi (Naher et al , 2011). Chlamydospores produced on CPA were slightly larger (mean 44.0 μm; n=50) than reported.…”
Section: Figuresupporting
confidence: 73%
“…Phytophthora chrysanthemi was first described as a new species on Chrysanthemum in Japan (Naher et al , 2011). In 2015, it was reported from Croatia (Tomiċ & Iviċ, 2015) and in 2016 from the USA (Randall‐Schadel, 2016).…”
Section: Figurementioning
confidence: 99%
“…Multi-gene phylogenies have shown that most of the 10 clades are monophyletic, except the Clades 4 and 9 (Blair et al 2008). Clade 9 is the most rapidly expanding, with most of its species recently described (Hong et al 2010(Hong et al , 2012Naher et al 2011;Rea et al 2011;Yang and Hong, 2013;Yang et al 2014a, b). Members of this clade generally produce non-papillate and non-caducous zoosporangia.…”
Section: Phytophthora De Barymentioning
confidence: 99%
“…Analyses of ITS and cox 1 sequences grouped P. hydrogena with P. aquimorbida (Hong et al 2012), P. hydropathica (Hong et al 2010), P. irrigata , P. chrysanthemi (Naher et al 2011) (only supported by ITS sequence), P. insolita (Ann and Ko FIG. 5.…”
Section: Discussionmentioning
confidence: 98%